KEPATUHAN BENDAHARA DESA DALAM MEMENUHI KEWAJIBAN PERPAJAKAN DALAM PRESPEKTIF TEORI PLANNED BEHAVIOR - Nina Andriana (Politeknik Keuangan Negara STAN, 2019)
This study aims to explore the problems faced by the Village Treasurer in fulfilling their tax obligations. This research is a descriptive explorative qualitative research. The study was conducted by analyzing the literature, regulations, theories, and research related to the treasurer's compliance in fulfilling his tax obligations, after which the writer made a synthesis to obtain a general picture of what was the problem for the Village Treasurer in fulfilling obligations the taxation. The Village Treasurer as the village representative in carrying out payments at the expense of the APBDes is given the obligation to withhold and collect income tax and other taxes under tax provisions. Results of deductions and tax collections must be deposited into the state treasury. However, according to the Directorate General of Taxes in pajak.go.id, it is known that most villages have not fully implemented their tax obligations. The non-compliance of the Village Treasurer in fulfilling his obligations when viewed from the perspective of the Planned Behavior Theory is caused by several factors including (1) the attitude of the treasurer's behavior that does not fully understand the importance of taxes for the nation and state, (2) subjective norms namely Village Treasurer do not feel that the implementation of taxation obligations is the desired action by the closest important people such as Central and Regional Governments, Village Heads as superiors, colleagues, and (3) Perception of behavioral control felt by Village Treasurers that implementation of tax obligations is sufficient complicated so that the Village Treasurer has not done it optimally. To increase the compliance of the Village Treasurer in fulfilling their obligations, it is necessary to provide an understanding to the Village Treasurer of their tax obligations, whether through training, outreach, or workshops. Also, the Village Head is expected to provide intensive guidance and supervision to the Village Treasurer in carrying out tax obligations by monitoring and requesting treasurer accountability reports regularly so that the Village Treasurer feels that reporting tax obligations is an important action according to important people around him. The role of the local government as a village supervisor is also needed to increase the obedience and compliance of the Village Treasurer through coaching by the Inspectorate.